2018
DOI: 10.1002/cam4.1700
|View full text |Cite
|
Sign up to set email alerts
|

Interferon gamma in cancer immunotherapy

Abstract: Immune system can recognize self vs transformed self. That is why cancer immunotherapy achieves notable benefits in a wide variety of cancers. Recently, several papers reported that immune checkpoint blockade therapy led to upregulation of IFNγ and in turn clearance of tumor cells. In this review, we conducted an extensive literature search of recent 5‐year studies about the roles of IFNγ signaling in both tumor immune surveillance and immune evasion. In addition to well‐known functions, IFNγ signaling also in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
197
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(205 citation statements)
references
References 50 publications
6
197
0
2
Order By: Relevance
“…INFG induces the expression of PD-L1 through increasing STAT1 signaling and decreasing STAT3 activation. In some studies, strong correlation between INFG and ICB response was reported [26] . In a study of NSCLC and UC, INFG signature is associated with TMB signature [27] .…”
Section: Discussionmentioning
confidence: 99%
“…INFG induces the expression of PD-L1 through increasing STAT1 signaling and decreasing STAT3 activation. In some studies, strong correlation between INFG and ICB response was reported [26] . In a study of NSCLC and UC, INFG signature is associated with TMB signature [27] .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, these pathways are also extensively reported in other processes such as immunosurveillance 157 , stem cell self-renewal 158 and epithelial to mesenchymal transition 159 . Some of these processes have already been described in endometriosis pathogenesis and they include Kras signalling 160,161 , MYC targets 162,163 , mTORC1 signalling [164][165][166] , PI3K AKT mTOR signalling [167][168][169][170] , TGF beta signalling [171][172][173] , interferon gamma [174][175][176][177] , and interferon alpha response 178,179 . In accordance with our data regarding microenvironment heterogeneity, certain pathways that are enriched in the stage III-IV phenotype are directly associated to M1-M2 macrophage polarization, and these pathways include TGF beta sinalling 180,181 , PI3K AKT mTOR signalling 151,182 , interferon gamma response 79 , adipogenesis, glycolysis and other metabolic reprograming pathways 183 .…”
Section: Discussionmentioning
confidence: 99%
“…Although IFNγ secreted by immune cells promotes growth arrest of tumors by augmenting MHC class I expression, contributing to the recruitment of effector cells, mediating Treg fragility and coordinating innate and adaptive antitumor responses (33,34), IFNγ signaling can also compromise antitumor immunity by blocking these activities through the induction of immune checkpoint inhibitory molecules on T and tumor cells (35). The overall balance and timing of IFNγ expression over the course of tumor development and the downstream consequences likely critically determine an effective vs. suppressive immune response and an immunologic profile of consideration for immunotherapeutic approaches to treatment (36).…”
Section: Discussionmentioning
confidence: 99%